CHILD ALCOHOLISM AS A SOCIAL AND PEDAGOGICAL PROBLEM - Kholova Mohigul Shavkatovna, Omonova Beautiful Normurod daughter (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
this in the article modern in society children between being observed alcoholism and addiction cases social pedagogical problem as analysis will be made in the article this negative of circumstances come exit factors, social environment and pedagogical effects with dependency scientific basically also, deviant behavior formation in the process pedagogical tasks, preventive measures and family of upbringing place about practical recommendations presented article youth upbringing with worker social educators, psychologists and teachers for useful source be takes.